2013
DOI: 10.1155/2013/964034
|View full text |Cite
|
Sign up to set email alerts
|

In VivoEvidence of Increased nNOS Activity in Acute MPTP Neurotoxicity: A Functional Pharmacological MRI Study

Abstract: 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin commonly used to produce an animal model of Parkinson's disease. Previous studies have suggested a critical role for neuronal nitric oxide (NO) synthase- (nNOS-) derived NO in the pathogenesis of MPTP. However, NO activity is difficult to assess in vivo due to its extremely short biological half-life, and so in vivo evidence of NO involvement in MPTP neurotoxicity remains scarce. In the present study, we utilized flow-sensitive alternating inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For FAIR MRI, the derivation of the CBF maps was according to our previous study . The VR was assessed using the level of CBF increase induced by carbogen switched from air in the region of interest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For FAIR MRI, the derivation of the CBF maps was according to our previous study . The VR was assessed using the level of CBF increase induced by carbogen switched from air in the region of interest.…”
Section: Methodsmentioning
confidence: 99%
“…For data acquisition and quantification of MRI (3D ΔR 2 ‐mMRA, BOLD MRI, and FAIR), drawing of regions of interest was performed using identical standard operating procedures …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major reported key events reported in the investigated studies comprise JNK activation Xia et al, 2001) and activation of NMDA receptors with subsequent increase in the intracellular Ca 2+ concentration (Siow et al, 2013). The inhibition of complex I activity (especially in the striatum and substantia nigra) (Dauer et al, 2002;Richardson et al, 2007) and mitochondrial dysfunction such as inhibition of mitochondrial respiration, mitochondrial enzyme deficiency and swollen mitochondria (Yang et al, 2009) have been demonstrated.…”
Section: Supporting Publications 2016: En-955 63mentioning
confidence: 90%
“…to intrathecal application. Rat (Hung et al, 2014;Siow et al, 2013), cat (Aznavour et al, 2012), and zebrafish (Sallinen et al, 2009) have also been used to study MPTP neurotoxicity but less frequent than mice and monkeys.…”
Section: Supporting Publications 2016: En-955 63mentioning
confidence: 99%